The Effect and Mechanism of Emodin on the NO Secretion of Human Umbilical Vein Endothelial Cells (HUVECs) Induced by High Glucose - Yajia Li; Qiangxiang Li; Chunyan Xie; Yanfei Huang; Limin Jia (International Journal of Endocrinology)
Objective. To investigate the effects of emodin on nitric oxide (NO) secretion induced by high glucose in human umbilical vein endothelial cells (HUVECs) through the p-Akt signaling pathway. Methods. Sensitivity of cells to emodin was determined by MTT assay to establish the experimental concentrations; then, HUVECs were treated with high-dose (33.3 mmol/L) glucose (HG), HG + emodin (HG + E), HG + the Akt phosphorylation inhibitor LY294002 (HG + LY), or HG + E + LY. The p-Akt (Ser 473) expression in 48 h was analyzed using Western blot. NO effect on the secretion of HUVECs was analyzed using nitrate reductase assay. Results. The sensitive emodin concentration for HUVECs growth was 10 mol/L (P<0.05). Compared with the HG group, NO secretion was significantly higher in the HG + E group (P<0.05), whereas it was lowest in the HG + LY group (P<0.05). Compared with the HG + LY group, NO secretion was increased in the HG + E + LY group (P<0.05). The p-Akt protein expression was decreased in the HG + LY group when compared to the HG group (P<0.05), while it significantly increased in the HG + E group (P<0.05). Compared with HG + LY group, p-Akt protein expression was significantly higher in the HG + E + LY group (P<0.05). Conclusion. Emodin could improve the NO secretion of HUVECs by high glucose through the p-Akt signaling pathway.